Gamificacion y su incidencia en el desarrollo cognitivo en niños de educación inicial - Ramírez Zuñiga, Adamaris Jimena (2024)
Gamification is a strategy that consists of the application of game elements and mechanics in gaming contexts, such as education, it is used to make the learning process more attractive and motivating, involving students in a playful way and providing a system of rewards that reinforce positive behaviors. The study aims to determine the impact of gamification on the cognitive development of children in initial education II of the "Gabriel García Moreno" Educational Unit in the Urdaneta Canton, Los Ríos. It is evident that students present cognitive deficiencies, generating concern among parents due to the perception of lack of comprehensive training in teachers. Children show difficulties in problem solving, teaching retention, and disinterest in learning. Given this problem, the need arises to evaluate and improve teaching to enhance cognitive development, crucial for attention, language and learning. Gamification emerges as an innovative technique, although its application is limited in fiscal establishments like this one. The study will use a mixed approach and documentary and field methods, involving children, teachers and parents. It is anticipated that the results will reveal the impact of gamification on cognitive development, providing valuable information to improve educational quality. The conclusions could highlight the effectiveness of gamification as a tool to stimulate cognitive skills in early education, highlighting the need for its implementation in educational environments such as the one mentioned.